Effect of Frozen Storage on the Water- Holding Capacity and pH of Broiler Chicken cut-up Parts (Gallus gallus domesticus) - Ghimire, Arjun; Parajuli, Pawan (Himalayan Journal of Science and Technology, 2020)
Broiler chickens (Gallus gallus domesticus) were collected from local chicken suppliers of Dharan (26.8065° N, 87.2846° E), Nepal, and slaughtered to prepare the cut-up parts (breast, drumstick, dorso, wings, and thigh). They were vacuum packed in polythene bags and frozen stored (-21.5 ±3.5ºC) for 45 days to study the effect of frozen storage on the water holding capacity (WHC) of meat. Cooking loss, drip loss, and pH changes were analyzed at 5 days intervals during storage and the data were analyzed using Genstat® v 12.1.The cut-up parts showed a significant change (p